2023
DOI: 10.1212/wnl.0000000000207268
|View full text |Cite
|
Sign up to set email alerts
|

Brain Shrinkage in Anti–β-Amyloid Alzheimer Trials

Abstract: One of the puzzling observations from anti–amyloid-β therapeutic trials for Alzheimer disease (AD) has been that treated arms fail to show preservation of brain volume. In this issue of Neurology®, Alves et al.1 presented a meta-analysis of anti–amyloid-β therapies and show that the agents do not slow the rate of brain volume loss. Depending on the class of drug, these new agents can even accelerate loss of whole-brain and hippocampal volume and increase ventricular volume. This association has been seen with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…It has been shown previously that levels of synaptic proteins can predict the rate of cognitive decline in human AD patients when measured post mortem (27) or with positron emission tomography (PET) (28). Interestingly, the reduced brain volume detected by T2-weighted MRI in the ultrasound-treated mice is consistent with other studies that have shown significantly increased brain volume loss in AD patients in clinical trials (29). It has been speculated that plaque removal may explain the volume loss, but this is unlikely the to be the reason given the small volume of brain taken up by plaques compared to the magnitude of changes found on MRI.…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown previously that levels of synaptic proteins can predict the rate of cognitive decline in human AD patients when measured post mortem (27) or with positron emission tomography (PET) (28). Interestingly, the reduced brain volume detected by T2-weighted MRI in the ultrasound-treated mice is consistent with other studies that have shown significantly increased brain volume loss in AD patients in clinical trials (29). It has been speculated that plaque removal may explain the volume loss, but this is unlikely the to be the reason given the small volume of brain taken up by plaques compared to the magnitude of changes found on MRI.…”
Section: Discussionsupporting
confidence: 84%
“…39 Lecanemab was not associated with loss of hippocampal volume, but ventricular enlargement and reductions in cortical thickness occurred in the treated group, 39 findings of uncertain significance. 40 The donanemab phase 2 trial, 29 the donanemab phase 3 trial (Lilly press release, 5-3-23), and the lecanemab phase 3 trial 36 imaging results (Figure 2) support a conjecture 41 that clinical success of the AAMAs is contingent on the thoroughness of amyloid removal as expressed by the percentage of treated Time in months is on the x-axis, and proportion of participants worsening by 1 global CDR point is on the y-axis for placebo group (black line) and lecanemab-treated group (green line). The numbers of at-risk participants are given for each group at each time point, below the x-axis.…”
Section: Amyloid Removal and Other Biomarkers In Aama Trialsmentioning
confidence: 99%
“…39 Lecanemab was not associated with loss of hippocampal volume, but ventricular enlargement and reductions in cortical thickness occurred in the treated group, 39 findings of uncertain significance. 40…”
Section: Lecanemab Phase 3 Clinical Trial and Beyondmentioning
confidence: 99%
“…2,9 Alternative mechanistic explanations for the observed loss of brain volume induced by amyloid-lowering monoclonal antibodies include a decrease in amyloid plaque volume, cerebral fluid shifts, and reduction in periplaque inflammation. 10 Some of these explanations have been advanced to suggest that observed loss of brain volume may represent benign changes similar to pseudoatrophy observed in patients with multiple sclerosis treated with disease-modifying drugs. Although definitive explanations for these MRI changes may require detailed neuropathological studies, they should not preclude reporting of associated clinical outcomes at the end of the randomized clinical trials.…”
mentioning
confidence: 99%